Characterization of bacterial community structure in bioremediation treatment of herbicide/dioxin contaminated soil at field trials - Huu, Nguyen Ba; Cam Ha, Dang Thi (Academia Journal of Biology, 2012)
Bioremediation technology has been successfully applied in detoxification at different scales of herbicide/dioxin contaminated soil in the US former military base at Da Nang Airport. PCR-DGGE technique was used for characterization of bacterial community structure in soil samples of biotreatment experiments at small field scales 0.5 m3 and 1.5 m3. There were differences on bacterial diversity level in the soil samples of biotreatments from 0.5DN1 to 0.5DN4. Lower diversity level was found in the soil sample 0.5DN4 and 0.5DN5 in comparison to three others. In other biotreatment scale 1.5 m3, the more bacterial diversity was also found in biotreatment experiments 1.5DN1, 1.5DN3 and 1.5DN4 than two other experiments 1.5DN2 and 1.5DN5. The sequence analysis of DNA clones that excised from DGGE gel, showed that these clones were belonged to 6 bacterial classes including Alphaproteobacteria, Betaproteobacteria, Gammaproteobacteria, Actinobacteria, Acidobacteria, Bacteroides and also unclassified bacteria. The results obtained from this study provide fundamental bases for enhancement the rate of detoxification of herbicide/dioxin as well as other toxic chemical contaminated soil in Vietnam.